2017
DOI: 10.3329/ajmbr.v3i2.33564
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacterial pathogens from egg shell, egg yolk, feed and air samples of poultry houses

Abstract: This study was selected to find out the bacterial pathogens in egg yolk, egg shell, feed and air samples of poultry houses at Dinajpur district in Bangladesh with isolation, identification and characterization of bacterial pathogens present in those samples. For this study, a total of 147 samples comprising egg shell (36), egg yolk (36), feed (45) and air (30) were collected during the period from January to May, 2012 and the collected samples were then examined for the bacteriological study by using cultural,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
1
2
2
2
Order By: Relevance
“…Almost similar prevalence of Salmonella spp. (23.52%) was also reported previously [30]. Contamination of egg by Salmonella spp.…”
Section: A Overall Prevalence Of Bacteria Isolated From Eggssupporting
confidence: 83%
“…Almost similar prevalence of Salmonella spp. (23.52%) was also reported previously [30]. Contamination of egg by Salmonella spp.…”
Section: A Overall Prevalence Of Bacteria Isolated From Eggssupporting
confidence: 83%
“…Out of 300 eggs, 58 (19.33%) eggshells yielded growth of Staphylococcus spp., which was supported by Syed et al [17] in Pakistan, who reported 21.3% prevalence of Staphylococcus spp. However, the prevalence found in our study was comparatively higher than the findings of Parveen et al [18], Eid et al [19], Chaemsanit et al [20], Pyzik et al [21], and Pyzik and Marek [22] who observed the prevalence was 5.5%, 14.5%, 18%, 7.61%, and 15.6% in Dinajpur (Bangladesh), Sharkia (Egypt), Thailand, and Lubin city, respectively. The prevalence of Staphylococcus spp .…”
Section: Discussioncontrasting
confidence: 94%
“…Penelitian Parveen et al (2017) menunjukkan bakteri yang ditemukan dalam kerabang telur diantaranya adalah Staphylococcus spp. (5.55%), Escherichia coli (11.11%), Salmonella serovars (2.77%) and Bacillus spp.…”
Section: Kematian Embriounclassified
“…(8.33%). Parveen et al (2017) juga menambahkan kontaminasi bakteri dipengaruhi oleh beberapa faktor yaitu lingkungan pembibitan, praktik pemuliaan, sistem perkandangan, letak geografis, dan musim. Selain itu, kontaminasi juga dapat terjadi selama transportasi telur dan atau pengemasan di peternakan atau di tempat penyimpanan, baik melalui lingkungan atau dari satu telur ke telur lainnya.…”
Section: Kematian Embriounclassified